The relationship of the Islamic Dawa Party with Islamic movements in its stages of change 1958-1979 AD (Eurasian Journal of History, Geography and Economics, 2023)
The establishment of the Islamic Dawa Party in 1957 AD in Iraq preceded the emergence of many Islamic movements and parties in Iraq and the Islamic world, which continued to appear even after its establishment. It is natural for him to have relations with her and stances towards her in his fields of work. This paper is to shed light on the nature of the relationship of the Islamic Dawa Party with those movements and parties in its stage's of change (1958-1979 AD). The study of the paper required to divide it into an introduction introducing the history of the party and the reasons that led to choosing the subject of the study and mentioning its most important sources, and a first topic that shed light on Islamic movements and parties in the Islamic world, in which it presented the multiplicity of Islamic movements and parties and dealt with the nature of the disagreement of those movements and parties. The second topic is entitled the nature of the Islamic Dawa Party's relationship with Islamic movements, in which it studied the intellectual bases of the Islamic Dawa Party's relationship with Islamic movements and the cooperation of the Islamic Dawa Party with Islamic movements